1994
DOI: 10.1038/369403a0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-cell activity antagonized by naturally occurring HIV-1 Gag variants

Abstract: Most asymptomatic individuals infected with HIV-1 have a cytotoxic T lymphocyte (CTL) response to the virus Gag proteins which can be demonstrated in vitro. Epitopes have been mapped in p17 Gag and p24 Gag restricted by HLA-B8 (p17-3 and p24-13) and -B27 (p24-14). Viruses isolated from patients who make CTL responses to these peptides vary within the genetic sequences encoding these epitopes and some mutations lead to reduction in killing activity in vitro. This was attributed to either failure of the variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
245
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(256 citation statements)
references
References 15 publications
9
245
2
Order By: Relevance
“…This is supported by data from Moore et al [25], showing that HIV-1 infected patients harbouring virus with escape mutations had a level of viraemia that was approximately a log higher than individuals infected with HIV-1 that lacked such mutations. In addition, it has been shown that cells expressing mutated HIV-1 peptides can even block the lysis of cells infected with unmutated virus [18]. In our current study however, the combined amino acid variation across the specific peptide regions studied was not associated with peripheral levels of HIV-1.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This is supported by data from Moore et al [25], showing that HIV-1 infected patients harbouring virus with escape mutations had a level of viraemia that was approximately a log higher than individuals infected with HIV-1 that lacked such mutations. In addition, it has been shown that cells expressing mutated HIV-1 peptides can even block the lysis of cells infected with unmutated virus [18]. In our current study however, the combined amino acid variation across the specific peptide regions studied was not associated with peripheral levels of HIV-1.…”
Section: Discussioncontrasting
confidence: 78%
“…The rapid replication kinetics and the low-fidelity RT enzyme of HIV-1 allow a high mutation rate, which enables the virus to evade host immune surveillance. Studies with CTLs have shown that mutations, even single amino acid changes, of viral sequences that specify immunogenic epitopes can lead to escape from CD8 T-cell recognition [18][19][20][21]25], impairing the ability of the host to control infection. Little data exists however on the influence of HIV-1 antigenic variation on HLA class II-restricted CD4 T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, positive selection might have occurred if peptide P4, a naturally occurring APL of TPO produced by professional antigen presenting cells, is presented in the thymus. ''Naturally'' occurring epitope variants, with APL characteristics, may have an important role in immune recognition and pathology has been demonstrated in viral infections (36,37). In these latter situations, however, the virus mutates changing amino acids in critical TCR contact sites and thus leading to the generation of ''naturally induced'' APL.…”
Section: Discussionmentioning
confidence: 99%
“…Other variations, primarily in solvent-accessible residues, may abrogate TCR recognition altogether or alter it in such a way that critical activation signals are not transmitted to the cytotoxic T cells resulting in attenuated responses or even anergy [10,[16][17][18] . Examples of attenuated responses have also been found with HIV and HBV [28][29][30][31][32] . It is thought that by antagonizing T-cell responses to native epitopes, viruses expressing mutant epitopes might aid in the survival of infected cells producing wild-type viruses, which would otherwise be recognized and destroyed by CTL.…”
Section: Introductionmentioning
confidence: 99%